Effect of Work-Based Learning Model on Students’ Achievement Motivation - Dwi Agus Sudjimat; Luchyto Chandra Permadi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
This study determines the effect of the Work-Based Learning (WBL) model on achievement motivation of students in the Study Program of Mechanical Engineering at Vocational High Schools (VHS) compared to the Training Within Industry (TWI) model. This study used a quasi-experimental research method with a factorial design in two groups of XII grade vocational high school students of mechanical engineering. The data in the form of achievement motivation was collected using a questionnaire. The data were analyzed using two way Anova technique with α of 0.05. The results showed that (1) the students taught using the WBL model had a significantly higher achievement motivation than the achievement motivation of students taught using the TWI model; (2) students with high prior knowledge had a significantly higher achievement motivation than the achievement motivation possessed by students with moderate and low prior knowledge; and (3) there is an interaction between the use of learning models and students' prior knowledge towards students' achievement motivation. The findings indicated that the WBL model has the potential to improve the quality of learning outcomes of vocational education, especially in increasing students' achievement motivation, compared to traditional learning using the TWI model.